Evolution of Food Systems: Social and Environmental Impacts - Vinci, Giuliana; Tiradritti, Margherita; Masiello, Luca (New Innovations in Economics, Business and Management Vol. 9, 2022)
With the rise of awareness about sustainability and new production processes, such as Circular Economy, and the publication of the 17 Sustainable Development Goals (SDGs) of the Agenda 2030 in 2015, food systems and urbanisation have become strictly linked to each other: at the increase of the urbanisation should correspond to the rise of the efficiency of food systems to ensure food security and food quality. Food waste could be considered a consequence of the inefficiency and inappropriate current consumption and production paths and food systems applied. The City Region Food Systems (CRFS) developed by the Food and Agriculture Organization (FAO) could offer cities crucial tools for more efficient food systems. The paper aims to analyse the CRFS model in line with the 17 SDGs for understanding the complex and systemic linkages between food systems and urbanisation and assess their social and environmental impacts.